Welfare economics in theory and practice - Price, Catherine M. (London : Macmillan, 1977)
This book is intended for second and third-year undergraduates and postgraduates who are studying the economic basis of public policy and is designed to provide a basic text for a variety of courses concerned with microeconomic decision-making.
Includes index.
Includes bibliographical references: p. 169-172.
rpm 02/11/2017
Loans
Keywords: Welfare economics; Great Britain